Fan Campaign Aksi Boikot Terhadap Kolaborasi Starbucks X NCT di Media Sosial X - Lavinia Tiara Malika; Kusuma, Ade (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
This study highlights the role of K-pop fandom, particularly Indonesian NCTzens, in a boycott campaign against the collaboration between NCT and Starbucks conducted on the X social media platform. Framed by a sensitive geopolitical context, this research employs a qualitative approach, utilizing non-participant observation of the @nct_menfess fanbase account and in-depth interviews with seven informants selected through purposive sampling. Data were analyzed thematically to understand patterns of digital communication, fan content production, and the mobilization of collective campaigns in online spaces. The findings reveal that the boycott campaign carried out by Indonesian NCTzens represents a form of participatory culture that goes beyond fan support and evolves into social advocacy. Digital strategies such as hashtag activism, fan edits, memes, and real-world actions like LED truck protests demonstrate that fandom communities hold potential as active civic agents in global public discourse. This study contributes to the understanding of fandom’s role as a social force in the digital age.